2022
DOI: 10.3390/molecules27165100
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrocurcumin-Related Vascular Protection: An Overview of the Findings from Animal Disease Models

Abstract: Tetrahydrocurcumin (THC), one of the major metabolites of CUR, possesses several CUR-like pharmacological effects; however, its mechanisms of action are largely unknown. This manuscript aims to summarize the literature on the preventive role of THC on vascular dysfunction and the development of hypertension by exploring the effects of THC on hemodynamic status, aortic elasticity, and oxidative stress in vasculature in different animal models. We review the protective effects of THC against hypertension induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…In the same direction, Nakmareong et al [7] showed that administration of a THC-containing diet in a rat model of N(omega)-Nitro-L-Arginine Methyl Ester (L-NAME)-induced oxidative stress leads to a significantly reduced production of superoxide (O2•) and malondialdehyde (MDA), followed by increased endogenous synthesis of glutathione (GSH) [8]. Similarly, THC significantly reduced L-NAME-induced aortic wall thickness and stiffness [9]. Ma et al [10], investigating the relationship between the antioxidative brain potential of brain tissue and cognitive impairment in a C57BL/6 mouse model induced by acute hypobaric hypoxia, discovered that THC improved cognitive impairment, accompanied by reduced oxidative stress and increased glucose transporter 1 (GLUT1) protein levels.…”
Section: The Structural Feature Of Thc Associated With Its Antioxidan...mentioning
confidence: 98%
See 1 more Smart Citation
“…In the same direction, Nakmareong et al [7] showed that administration of a THC-containing diet in a rat model of N(omega)-Nitro-L-Arginine Methyl Ester (L-NAME)-induced oxidative stress leads to a significantly reduced production of superoxide (O2•) and malondialdehyde (MDA), followed by increased endogenous synthesis of glutathione (GSH) [8]. Similarly, THC significantly reduced L-NAME-induced aortic wall thickness and stiffness [9]. Ma et al [10], investigating the relationship between the antioxidative brain potential of brain tissue and cognitive impairment in a C57BL/6 mouse model induced by acute hypobaric hypoxia, discovered that THC improved cognitive impairment, accompanied by reduced oxidative stress and increased glucose transporter 1 (GLUT1) protein levels.…”
Section: The Structural Feature Of Thc Associated With Its Antioxidan...mentioning
confidence: 98%
“…THC reduces cytochrome c homocysteinylation by decreasing oxidative stress and matrix metalloproteinase 9 (MMP9), as well as protecting neurons via autophagic mechanisms. [9]. The BBB could be disrupted in a variety of clinical situations, including I/R injury, which causes increased vascular permeability and the formation of cerebral edema [74].…”
Section: Thc-related Induction Of Mitochondrial Apoptotic Route Autop...mentioning
confidence: 99%
“…Vascular remodeling is thought to be an important feature of human aging, loss of arterial elasticity is common as people age ( 12 , 13 ). But at the individual level, vascular remodeling is actually a dynamic process, influenced by life style, genetic/epigenetic factors, and biological cues ( 14 16 ). Diabetes is an important risk factor for vascular remodeling, which can cause extracellular matrix changes, eventually leading to arterial remodeling and arterial stiffness ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other CUR analogues and some natural products, EF24 offers distinct advantages, primarily stemming from its engineered properties, pro-apoptotic effects, and its potential role as a targeted therapy in the context of cancer treatment [4][5][6][7][8][9]. Actually, it is crucial to acknowledge that most of the mentioned analogues come with certain limitations.…”
Section: Introduction 1structurally Related Mechanisms Of Actionmentioning
confidence: 99%
“…Actually, it is crucial to acknowledge that most of the mentioned analogues come with certain limitations. These limitations can be attributed to either weak bioavailability or a trade-off between their more pronounced antioxidant or anti-inflammatory effects and their efficacy in combating cancer [4][5][6][7][8][9]. Taking into consideration these inherent characteristics and limitations, EF24 stands out as one of the most suitable and potent options.…”
Section: Introduction 1structurally Related Mechanisms Of Actionmentioning
confidence: 99%